Influence of ligand composition on crystal structure formation – isostructurality and morphotropism. Issue 2 (25th November 2020) - Arhangelskis, Mihails; Van Meervelt, Luc; Dobrzańska, Liliana
Abstract : The replacement of an H-atom with a Me-group leads to the isostructurality of polymeric Ag(i ) complexes, whereas it causes morphotropic adjustments in the parent ligands (discrete molecules). Abstract : Two new Ag(i ) complexes with 1, 3-bis(imidazol-1-ylmethyl)benzene (L1 ) and 1, 3-bis(imidazol-1-ylmethyl)-5-methylbenzene (L2 ), namely [AgL1 ]CF3 SO3 n (1 ) and [AgL2 ]CF3 SO3 n (2 ), were synthesised and characterised by SCXRD to uncover the effect that introducing a methyl group to the benzene core of the ligand has on the molecular/crystal structure of the metal complex. The studies revealed a high level of isostructurality of the formed Ag(i ) complexes, consisting of 1D cationic chains with the charge neutralised by the counterions applied. These results triggered structural investigations of the parent ligands, which, as revealed by SCXRD, crystallise as dihydrates in different space groups of a monoclinic system. Further analyses revealed that the motifs in their molecular packing in general stay the same. However, some morphotropic/positional adjustments are taking place in L2 to accommodate the presence of the methyl substituent.